2013
DOI: 10.1128/aac.01129-13
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Mefloquine and Enpiroline Is Highly Influenced by a Chronic Schistosoma mansoni Infection

Abstract: cChronic Schistosoma mansoni infections lead to severe tissue destruction of the gut wall and liver and can influence drug disposition. This study aimed to investigate the impact of a chronic S. mansoni infection on the pharmacokinetic (PK) parameters of two promising antischistosomal lead candidates (mefloquine and enpiroline) in mice. Studies were conducted in two different mouse cohorts (S. mansoni-infected and uninfected mice) for both drugs. Plasma samples were collected at various time points after oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(45 reference statements)
3
5
0
Order By: Relevance
“…The dosing regimen used for the treatment with PHX was based on the recently reported pharmacokinetics (PK) of PHX in healthy C57BL/6 mice [ 30 ] and the consideration that a higher exposure could be potentially expected in infected animals. This hypothesis is in accordance with previously reported data showing an increased plasmatic concentration of PZQ and other schistosomicidal compounds in mice and humans infected with Schistosoma [ 40 42 ].…”
Section: Resultssupporting
confidence: 94%
“…The dosing regimen used for the treatment with PHX was based on the recently reported pharmacokinetics (PK) of PHX in healthy C57BL/6 mice [ 30 ] and the consideration that a higher exposure could be potentially expected in infected animals. This hypothesis is in accordance with previously reported data showing an increased plasmatic concentration of PZQ and other schistosomicidal compounds in mice and humans infected with Schistosoma [ 40 42 ].…”
Section: Resultssupporting
confidence: 94%
“…Our results corroborate those reported by other authors for the liver and show that the elimination of drugs via both CYP and phase II of drug metabolism such as GST and UGT may be severely impaired during murine chronic schistosomiasis [35]. In fact, it has been demonstrated that chronic S. mansoni infection influence the pharmacokinetic profiles of some drugs, such as praziquantel, enpiroline and mefloquine, leading to delayed clearance [36,37]. Accordingly, given that schistosomiasis is prevalent in countries where coinfection for diseases such as HIV or malaria is common, it is important to ask how schistosomiasis affects the enzymes responsible for the metabolism of drugs given to treat not only schistosomiasis but also these coinfections [35].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, ARA schistosomicidal activity in experimental animals was faithfully reproduced in clinical trials at variance from mefloquine, which showed highly significant schistosomicidal action in mice and hamsters but poor efficacy in a randomized, exploratory human trial. [36][37][38][39][40] ARA seemed a far more promising schistosomicidal remedy than myrrh (Mirazid), which showed a low (10-15%) cure rate and low egg reductions in uncured individuals, regardless of the patients' ages or pre-treatment intensities of infection. [41][42][43] Despite that a 100% cure was reported after PZQ treatment of S. mansoni infections in eastern Sudan, 44 complete cures have seldom, if ever, been achieved in endemic areas after PZQ treatment.…”
Section: Discussionmentioning
confidence: 99%